South African natives’ conduct towards illegal migrants : a human rights approach - Mafa, Prudence; Makhubele, Jabulani Calvin; Matlakala, Frans Koketso; Baloyi, Themba Victor; Rabotata, Nthabeleng Enoch; Masilo, Daniel Tuelo; Kwakwa, Motshidisi Marbel; Mabasa, Matimba Allan (Penerbit Universiti Kebangsaan Malaysia, 2021)
South Africa has the largest number of migrant populations in Africa due to its relatively stable economy as compared to other African countries. A considerable number of these migrants are living in the country without proper documentation. This study sought to determine how migrants are treated by native South African citizens. Data for this body of work was collected following the COVID-19 regulations by way of focus group and semi-structured individual interviews. Five African-born foreigners from Southern Africa were interviewed in a focus group to solicit the treatment that they receive from South African citizens and authorities. A further two foreigners were individually interviewed to obtain their experiences. A thematic analysis was utilised to analyse data obtained from the participants. It emerged from the themes that undocumented migrants tend to live in isolation. This stems from a lack of trust by locals. The status of foreign nationals in the country makes it difficult for them to access basic services such as healthcare, safety and security services, and education. This obstacle makes it challenging for migrants to enjoy good quality life, which is an inherent human right. There is a need to protect human rights of foreign-born nationals, including undocumented migrants.